2021
DOI: 10.1007/s11748-021-01629-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical considerations for atrial functional regurgitation of the mitral and tricuspid valves based on the etiological mechanism

Abstract: Atrial functional mitral regurgitation is a hot research topic in the field of mitral valve disease. Atrial functional mitral regurgitation is distinctly different from ventricular functional mitral regurgitation. The surgical indications for atrial functional mitral regurgitation have not been well established because of the small amount of evidence gathered to date. Mitral annular plication with an artificial ring is an essential surgical procedure because dilatation of the mitral valve annulus is a main fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Long-standing atrial fibrillation is also associated with severe right and left atrial enlargement, usually with MR and TR, which requires additional atrial reduction surgery ( 17 ). Severe atrial enlargement leads to smoke-like flow in the atrium with a possibility of thrombosis and compression of the bronchus and lung, followed by decreased respiratory function ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-standing atrial fibrillation is also associated with severe right and left atrial enlargement, usually with MR and TR, which requires additional atrial reduction surgery ( 17 ). Severe atrial enlargement leads to smoke-like flow in the atrium with a possibility of thrombosis and compression of the bronchus and lung, followed by decreased respiratory function ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoprolapse of the anterior mitral leaflet can usually be corrected with restrictive annuloplasty. 91 The role of restoring sinus rhythm during surgery for mitral valve repair in patients with AFMR has not been clearly defined. One retrospective study found that patients who underwent concurrent Cox maze IV procedures experienced 94% freedom from recurrent MR after 3 years compared with only 44% among those who did not.…”
Section: Surgerymentioning
confidence: 99%
“… 91 Additional techniques, such as surgical AF ablation, LA appendage ligation, or LA plication around the MA, play an important role in this specific population of patients. 92 Surgical ablation procedures for paroxysmal and persistent AF during concomitant MV and TV surgery include full bi-atrial Cox–Maze procedure, pulmonary vein isolation, alone or combined with LA lesion sets, and hybrid procedure. 93 Patients with A-SMR undergoing surgical MV repair and concomitant Maze procedure had a lower incidence of heart failure and AF and lower recurrence rates of moderate–severe MR and TR at follow-up than those who underwent catheter ablation procedure.…”
Section: Treatment Of Atrial Secondary Tricuspid Regurgitationmentioning
confidence: 99%